Progress in Ratification and Implementation of ASEAN Protocols and Agreements in the Philippine Transport Sector - Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2012)
ASEAN transport cooperation is a key issue in the preparation for an ASEAN Economic Community in 2015. Transport cooperation requires member countries to ratify and sign protocols and agreements that will liberalize the transport sector in ASEAN. The transport sector in this study covers maritime and air transport. This paper examines the progress made by the Philippines in the ratification and implementation of protocols and agreements bearing on the transport sector, and discusses perceived barriers to ratification and implementation. There is a great need for policymaker's attention to the issue of airport infrastructure deficiencies and other limitations. The Philippines needs very badly an efficient air and maritime transport system in view of its archipelagic geographic condition, and its goal to have better, more efficient, and stronger linkages with regional and global markets. Investments to modernize the country's international ports and airports are obviously needed.
Keywords: 330; Philippines; maritime transport; logistics; freight forwarders; population aging; elderly work activity; old-age support; labor income age profile; consumption by income group